Comparação dos métodos parasitológico, imunológico e molecular em amostras de fezes de ratos (Rattus norvegicus Wistar) imunossuprimidos experimentalmente infectados por Strongyloides venezuelensis - Chaves, Leilane Alves (2014)
The diagnosis of strongyloidiasis is difficult the irregular larval excretion and in most cases, individuals are asymptomatic; detection of latent cases of Strongyloides stercoralis in immunosuppressed may decrease morbidity and mortality. In this sense, the improvement of reliable diagnostic methods is essential. The objective of the study was to compare the release of eggs in the feces by the technique of Egg counts per gram of feces (EPG), coproantigens detection by ELISA (Enzyme Linked Immunosorbent Assay) and amplification bands by conventional (Polymerase Chain Reaction) PCR from feces of non immunosuppressed and immunosuppressed mice experimentally infected with Strongyloides venezuelensis. In the experimental kinetic days 0 and 5, 8, 13, and 21 after infection p.i. were used. Comparing the EPG, coproantigens detection by ELISA and PCR, it was observed in the non immunosuppressed group the release of eggs from the EPG test day on 5 to day 13 p.i, being absent on day 21 p.i. Coproantigen positivity was observed in 33.3% 5 and 8 p.i. and 100% on days 13:21 p.i. and PCR, the presence of amplified bands was observed along the entire kinetics. In immunosuppressed animals, 100% of the released eggs in the feces, the data of the ELISA, 100% of the animals were evaluated in both positive and PCR, the presence of amplified bands during kinetics. It is concluded that detection of coproantigens by ELISA and PCR diagnosis could be useful tools for diagnosis of strongyloidiasis especially in cases of immunosuppression.